Pengaruh Service Excellence terhadap Kepuasan Tamu pada Industri Perhotelan: Studi pada Swiss-Belresort Dago Heritage Bandung - Aji Suandi, Muhamad; Fatimah, Siti (Puslitabmas Batam Tourism Polytecnic, 2026)
This study examines the effect of service excellence on customer satisfaction at Swiss-Belresort Dago Heritage Bandung. The research is motivated by increasing competition in the hospitality industry, where service quality plays a critical role in maintaining customer satisfaction and competitiveness. A quantitative approach was employed using a survey method, with data collected from 100 hotel guests selected through purposive sampling. Data were analyzed using simple linear regression. The findings reveal that service excellence has a significant positive effect on customer satisfaction (β = 0.960; p < 0.05), with a coefficient of determination (R²) of 92.2%. This indicates that service excellence contributes substantially to customer satisfaction. Key dimensions, including ability, attitude, appearance, attention, action, and accountability, play an important role in shaping positive guest perceptions. The study also identifies the presence of a service gap, particularly in terms of responsiveness and service consistency, which may affect the overall customer experience. Therefore, improving service consistency, employee performance, and responsiveness is essential to enhance customer satisfaction and strengthen competitiveness in the hospitality industry.